PENINGKATAN KREATIVITAS SISWA DALAM PEMBELAJARAN SENI BUDAYA DI KELAS VII.3 SMP NEGERI 3 KECAMATAN GUGUAK - Umma, Rahma Fitri; Chairul Haq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the learning process and student outcomes in improving creativity in Cultural Arts for class VII.3 at SMP Negeri 3 Guguak District. It used a descriptive qualitative method with data collected through observation, interviews, documentation, and literature review. The results show that learning is still theory-dominated with limited time, resulting in low student creativity. Improvement was carried out through practical activities of making bamboo flower vases with flora and fauna decorative motifs. The findings indicate increased creativity, seen in students’ ability to develop ideas, combine motifs, and apply more varied colors, although neatness and color composition still need improvement. In conclusion, practice-based learning is effective in enhancing student creativity in decorative art materials.